Remote Learning, COVID-19, and Children With Disabilities - Kate Henley Averett (SAGE Publishing, 2021)
While the COVID-19 pandemic affected the education of nearly all schoolchildren worldwide, pandemic-related school closures did not affect all children in equal ways. Between March and August, 2020, I interviewed 31 parents of children with disabilities as part of a larger interview study of U.S. parents of children in grades K-12. In this article, I analyze these parents' narratives about their families' experiences of pandemic-related remote learning to identify the particular challenges children with disabilities and their families faced with remote learning. I find that most, but not all, families struggled with remote learning, both when children's specific needs while learning at home differed from their needs at school, and when schools failed to provide adequate accommodations and services remotely. These narratives demonstrate how children with disabilities are particularly vulnerable to the type of large-scale systemic shock to U.S. public education that the pandemic has presented.